Local Connections of Layer 5 GABAergic Interneurons to Corticospinal Neurons - Tanaka, Yasuyo H.; Tanaka, Yasuhiro; Fujiyama, Fumino; Furuta, Takahiro; Yanagawa, Yuchio; Kaneko, Takeshi (Frontiers in Neural Circuits, 2011)
In the local circuit of the cerebral cortex, GABAergic inhibitory interneurons are considered to work in collaboration with excitatory neurons. Although many interneuron subgroups have been described in the cortex, local inhibitory connections of each interneuron subgroup are only partially understood with respect to the functional neuron groups that receive these inhibitory connections. In the present study, we morphologically examined local inhibitory inputs to corticospinal neurons (CSNs) in motor areas using transgenic rats in which GABAergic neurons expressed fluorescent protein Venus. By analysis of biocytin-filled axons obtained with whole-cell recording/staining in cortical slices, we classified fast-spiking (FS) neurons in layer (L) 5 into two types, FS1 and FS2, by their high and low densities of axonal arborization, respectively. We then investigated the connections of FS1, FS2, somatostatin-immunopositive (SOM) and other (non-FS/non-SOM) interneurons to CSNs that were retrogradely labeled in a Golgi-like manner in motor areas. When close appositions between the axon boutons of the intracellularly labeled interneurons and the somata/dendrites of the retrogradely labeled CSNs were examined electron-microscopically, 74% of these appositions made symmetric synaptic contacts. The axon boutons of single FS1 neurons were 2–4-fold more frequent in appositions to the somata/dendrites of CSNs than those of FS2, SOM and non-FS/non-SOM neurons. Axosomatic appositions were most frequently formed with axon boutons of FS1 and FS2 neurons (approximately 30%) and least frequently formed with those of SOM neurons (7%). In contrast, SOM neurons most extensively sent axon boutons to the apical dendrites of CSNs. These results might suggest that motor outputs are controlled differentially by the subgroups of L5 GABAergic interneurons in cortical motor areas.